Sleep and Trauma Effects of the Earthquake: A Cross‐Sectional Study - Karaahmetoğlu, Gülşen Ulaş; Arabaci, Zeynep (Wiley, 2025)
ABSTRACTAimThe present study was carried out in order to determine the effects of earthquakes on the sleep quality of earthquake survivors.DesignThe study is a cross‐sectional and descriptive design.MethodsThe research was conducted in the provinces affected by the earthquake, which occurred in Türkiye on 6 February 2023. The study was completed with 428 individuals affected by an earthquake, who voluntarily agreed to participate. Data were collected by using Google Forms and face‐to‐face data collection. The data collection instruments used here were the Descriptive Information Form, Emotion Assessment Scale for Traumatic Events (EASTE) and Pittsburgh Sleep Quality Index (PSQI).ResultsIt was determined that the average scores obtained from the PSQI scale by an individual affected by an earthquake were 11.10 ± 3.44 and they had poor sleep quality. The total EASTE score was 57.93 ± 16.3 points; the mean score from the trauma exposure subscale was 27.44 ± 8.14 points and the mean score from the trauma coping subscale was 30.50 ± 8.91 points, indicating that an individual affected by an earthquake was significantly affected by the trauma.ConclusionIt was also determined that providing physical and psychosocial support for individuals who experienced the earthquake in the short and long term is crucial for their sleep quality, quality of life and overall well‐being.Relevance to Clinical PracticeIt is an important study in terms of raising awareness that traumatic situations such as earthquakes affect both the physical and mental health of the individual, and nurses plan the care process on this issue.Patient or Public ContributionThe scales were filled in by individuals who experienced the earthquake.
Keywords: Male; Adult; Turkey; Empirical Research Quantitative; RT1-120; sleep quality; Nursing; Middle Aged; trauma; Cross-Sectional Studies; Sleep Quality; earthquake; Surveys and Questionnaires; Earthquakes; Humans; Female; community health nursing; Survivors; Sleep; Aged